2020
DOI: 10.3390/ma13173713
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Doxorubicin-Loaded Amphiphilic Poly(D,L-Lactide-Co-Glycolide)-b-Poly(N-Acryloylmorpholine) AB2 Miktoarm Star Block Copolymers for Anticancer Drug Delivery

Abstract: Owing to their unique topology and physical properties, micelles based on miktoarm amphiphilic star block copolymers play an important role in the biomedical field for drug delivery. Herein, we developed a series of AB2-type poly(D,L-lactide-co-glycolide)-b-poly(N-acryloyl morpholine) (PLGA-b-PNAM2) miktoarm star block copolymers by reversible addition–fragmentation chain–transfer polymerization and ring-opening copolymerization. The resulting miktoarm star polymers were investigated by 1H NMR spectroscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the area of drug delivery, the utilization of P­(NAM) is still in its infancy. Up to now, only a few reports have focused on its utilization as the hydrophilic backbone in polymer drug conjugates or as the hydrophilic component in amphiphilic block copolymer micelles. In addition, P­(NAM) was used to modify the surface of the synthetic liposomes with a hydrophilic shell. Here, it was shown that its protein-repellent properties were able to increase circulation time and prevent accelerated blood clearance in rats …”
Section: Introductionmentioning
confidence: 99%
“…In the area of drug delivery, the utilization of P­(NAM) is still in its infancy. Up to now, only a few reports have focused on its utilization as the hydrophilic backbone in polymer drug conjugates or as the hydrophilic component in amphiphilic block copolymer micelles. In addition, P­(NAM) was used to modify the surface of the synthetic liposomes with a hydrophilic shell. Here, it was shown that its protein-repellent properties were able to increase circulation time and prevent accelerated blood clearance in rats …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, copolymers containing, e.g., poly(ethylene oxide) as hydrophilic block and poly(L-amino acid) as hydrophobic block, can aggregate in water to micelles [6]. The core of the micelles can be loaded with a drug for the use as long-circulating drug carriers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…An additional procedure for postpolymerization modification is the degradation of the end group by irradiation with UV light [ 29 ]. After such an end-group modification, these polymers can be applied, e.g., for optoelectronic applications [ 30 ] or pharmaceutical purposes such as drug [ 31 ] or gene delivery [ 32 ].…”
Section: Introductionmentioning
confidence: 99%